What is the Use of Neoliberalism and Neoliberalisation? Contentious Concepts between Description and Explanation - Ernesto d'Albergo (Coordinamento SIBA, 2016)
The growing interest in neoliberalism and neoliberalisation has produced a wave of academic production, but also criticisms toward these concepts. They concern the conditions under which they may actually work as both/either explanans and/or explanandum of transformations affecting contemporary societies. The main accusations made are presented and compared with the actual uses of these catego-ries, building above all on the applications made in the articles that follow in this special issue. It is argued that this pair of concepts may help to detect critical processes descriptively, but so far it has not been able to provide explanations. Working more as descriptors, or identifiers of processes and out-comes they, rather, provide indirect paths to explanation, by becoming explananda themselves. It is easier to understand the "why" of social processes and changes starting from these concepts and turning to oth-er "real" theories than by direct use of them. In order to do that we need to operationalize neoliberalism and neoliberalisation as articulated ideal types, so as to take into account the existing varieties of policies, practices and relationships. This is still to be done and looks a lot like being a collective effort based on cumulative research and theorization.